Institutional Roles of Islamic Microfinance in Countering Informal Moneylenders: Evidence from Rural Communities - Yona Fitri; Khaidar Rahmaini Jamila; Yekti Mahanani; Muslim Marpaung (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Purpose: This study examines the role of PNM Mekaar Syariah in preventing the expansion of informal moneylending practices in rural communities, particularly among women micro entrepreneurs with limited access to formal financial services. It focuses on how Islamic microfinance mechanisms and group based empowerment reduce dependence on usurious lending. Method: A qualitative ethnographic approach was employed through participant observation, semi structured interviews, and field immersion within selected rural beneficiary groups. Data were thematically analyzed to capture patterns of financial behavior, social capital formation, and changes in borrowing practices. Results: The findings indicate that PNM Mekaar Syariah strengthens financial discipline, enhances entrepreneurial capacity, and builds trust based social capital through group financing structures. Beneficiaries demonstrate increased financial autonomy and a notable decline in reliance on informal moneylenders. Nevertheless, the study identifies the need for continuous financial education and digital payment integration to ensure long term sustainability. Implication: The study highlights Islamic microfinance as an effective community based strategy for preventing predatory lending and promoting sustainable financial inclusion in rural areas. Originality: This research offers ethnographic insights into Islamic microfinance by integrating social, behavioral, and religious dimensions in addressing informal moneylending practices in rural Indonesia.